Pola dan Wacana Pemahaman Hadis Penciptaan Perempuan dalam Situs Islam Online: Studi atas almanhaj.or.id, nu.or.id, dan mubadalah.id - Mukaromah, Kholila (Canonia Religia, 2025)
The hadith narrative that women are created from ribs is often used to legitimize social constructions that place women subordinately in gender relations. In the context of the digital era, this narrative not only develops in oral tradition and printed texts but is also reproduced and contested through new media. This article aims to analyze the patterns of understanding and discourse that develop in three online Islamic websites in Indonesia -almanhaj.or.id, nu.or.id, and mubadalah.id- towards the hadith of the creation of women from a rib. This research uses a qualitative approach based on discourse analysis and integrating hadith, gender, and media studies. The results show that each site constructs the meaning of the hadith following the religious ideology adopted: almanhaj.or.id represents a textual-conservative approach with the reinforcement of women's domestic role and inferiority; nu.or.id combines a moderate literal and contextual approach; while mubadalah.id carries a progressive interpretation with a mubadalah perspective that emphasizes equality in gender relations. All three show how digital media has become essential in contesting the meaning of religious texts and forming public opinion. This study concludes that the interpretation of hadith in online media is neither theologically nor ideologically neutral but rather determines the dominant narrative that develops about women in Islam. The findings contribute to developing contemporary hadith studies, especially in digital media and gender discourse.